(untitled) (Contemporary Journal of Social Science Review, 2024)
The current study tries to investigate the effect of public debt on the economic growth of the Pakistan with the moderation effect of development and non-development expenditures on the relationship of public debt and economic growth. The econometric technique Ordinary Least square (OLS) is used for the time series data over the period of 1972-2021 in this study. After conducting the OLS Method for the period of 49 years, the empirical findings of this study show that PD, NONEXP, DI, FDI, LFPR has statistically significant and positive impact on the GDP of the Pakistan. While the DEXP has statistically significant and negative impact on the economy. The moderation impact of PD*NONEXP and DI*NONEXP have statistically significant and negative impact on the GDP of the Pakistan. Results of the study suggest that governments and policymakers would made those policies in which further income could be generated and pay the debt services. When the excessive income is spent on the development projects then its impact become to start inverse on the economic growth of the country. So, there is also a need to be consideration to made the required expenditures on the development projects by the governments and policymakers.